Penguatan Pendidikan Karakter Berbasis Nilai-nilai Kristiani di Sekolah Menengah - Shasha Fazhiera; Esti Andari; Wulan Apriliani (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the implementation of character education based on Christian values ​​in the secondary school curriculum. This approach aims to form students who are not only academically superior but also have strong moral integrity. This study was conducted through qualitative methods by interviewing Christian religious teachers and students. The results show that the values ​​of love, justice, and responsibility have a significant impact on building student character. This article recommends integrating Christian values ​​more explicitly into the learning process.